Dynamics of Individual Correlogram of Identity Formation Stages of a University Student - Kaptsov, Alexander; Kolesnikova, Ekaterina; Panov, Viktor (Saratov State University, 2020)
The relevance of the study of identity formation stages of a university student is determined by changes in modern Russian higher education primarily related to digitalization processes. The article presents the description of students' identity formation features under conditions of higher education digitalization. The expediency of using an ecopsychological (ontological) model of identity formation is shown, according to which the process of formation of subject qualities is viewed in the ontological continuum, i.e. "subject of spontaneous activity - subject of arbitrary action". With this model used as a theoretical basis, the aim of the study was to empirically identify correlation relationships (correlograms) between the stages of identity formation in university students. We have put forward a hypothesis that the relationships between stages of identity formation are peculiar and describe the individual style of learning actions of a student in the temporal aspect. The necessity of using specifically developed methods of process diagnostics and nonparametric statistical methods has been shown. The results of a longitudinal study of the identity formation stages in the course of education at a technical university are presented (n = 150 students; first and second year students; M = 18,86 years; Sd = 0,79; 46% male), longitude duration is 8-10 weeks. There is an example of a correlogram, which demonstrates individual structure of correlation interrelations between the stages of student's identity. Interpretations of this structure of interrelations are suggested taking into account the style of subjectivity formation. Recommendations on application of obtained data regarding the stages of identity formation in the university educational process are given.